17O NMR Studies of Yeast Ubiquitin in Aqueous Solution and in the Solid State. (6th November 2020) - Lin, Binyang; Hung, Ivan; Gan, Zhehong; Chien, Po‐Hsiu; Spencer, Holly L.; Smith, Steven P.; Wu, Gang
Abstract: We report a general method for amino acid‐type specific 17 O‐labeling of recombinant proteins in Escherichia coli . In particular, we have prepared several [1‐ 13 C, 17 O]‐labeled yeast ubiquitin (Ub) samples including Ub‐[1‐ 13 C, 17 O]Gly, Ub‐[1‐ 13 C, 17 O]Tyr, and Ub‐[1‐ 13 C, 17 O]Phe using the auxotrophic E. coli strain DL39 GlyA λDE3 ( asp C − tyr B − ilv E − gly A − λDE3). We have also produced Ub‐[η‐ 17 O]Tyr, in which the phenolic group of Tyr59 is 17 O‐labeled. We show for the first time that 17 O NMR signals from protein terminal residues and side chains can be readily detected in aqueous solution. We also reported solid‐state 17 O NMR spectra for Ub‐[1‐ 13 C, 17 O]Tyr and Ub‐[1‐ 13 C, 17 O]Phe obtained at an ultrahigh magnetic field, 35.2 T (1.5 GHz for 1 H). This work represents a significant advance in the field of 17 O NMR studies of proteins. Abstract : Last piece of the puzzle : We report amino acid‐type specific incorporation of 17 O isotope into yeast ubiquitin with an auxotrophic E. coli strain. We show that 17 O NMR signals from 17 O‐labeled proteins can be observed both in aqueous solution and in the solid state.